Highly accurate surface and volume integration on implicit domains by means of moment‐fitting. (3rd September 2013) - Müller, B.; Kummer, F.; Oberlack, M.
SUMMARY: We introduce a new method for the numerical integration over curved surfaces and volumes defined by a level set function. The method is based on the solution of a small linear system based on a simplified variant of the moment‐fitting equations. Numerical experiments suggest that the accuracy of the resulting quadrature rules exceeds the accuracy of traditional methods by orders of magnitude. Using moments up to an order of p, the measured experimental orders of convergence exceed h p . Consequently, their construction is very efficient because only coarse computational grids are required. The conceptual simplicity allows for the application on very general grid types, which is demonstrated by numerical experiments on quadrilateral, triangular and hexahedral grids. Copyright © 2013 John Wiley & Sons, Ltd.